Ansiedad como consecuencia del aislamiento social frente al COVID - 19 en adolescentes. - Solange Monserrath, Criollo Ñacato (2021)
ABSTRACT Anxiety is an emotional state that can appear as an adaptive reaction or a symptom of psychological distress. Social isolation has increased the prevalence of anxiety in the population. The study's objective was to analyze the symptoms of anxiety as a consequence ofsocial isolation against COVID-19 in adolescents. A documentary and descriptive bibliographic review were carried out, with a quantitative approach, made up of a population of 878 manuscripts published between 2015 and 2021 in Google Scholar, ProQuest, Scielo, Dialnet; and a sample of 40 documents was collected. The results obtained were that anxiety affects the adolescent population, in a considered percentage, in Latin America and Europe asa consequence of social isolation due to COVID 19. In addition to adolescents, they are the population with the highest risk of suffering symptoms of anxiety or depression. Therefore, social isolation is one of the fundamental causes for the increase in anxiety symptoms in the adolescent population since this event alters the stage of psychosocial development, especiallydue to adaptation difficulties. Key Words: anxiety, social isolation, COVID-19, adolescents, mental health